2016
DOI: 10.1117/12.2241256
|View full text |Cite
|
Sign up to set email alerts
|

Aerial thermography for energy efficiency of buildings: the ChoT project

Abstract: The ChoT project aims at analysing the potential of aerial thermal imagery to produce large scale datasets for energetic efficiency analyses and policies in urban environments. It is funded by the Italian Ministry of Education, University and Research (MIUR) in the framework of the SIR 2014 (Scientific Independence of young Researchers) programme. The city of Bologna (Italy) was chosen as the case study. The acquisition of thermal infrared images at different times by multiple aerial flights is one of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The project was entitled "the Challenge of remote sensing Thermography as indicator of energy efficiency of buildings" (ChoT). It was funded by the Italian Ministry of Education, University and Research (MIUR) in the framework of the SIR 2014 (Scientific Independence of young Researchers) programme [121].…”
Section: Critical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The project was entitled "the Challenge of remote sensing Thermography as indicator of energy efficiency of buildings" (ChoT). It was funded by the Italian Ministry of Education, University and Research (MIUR) in the framework of the SIR 2014 (Scientific Independence of young Researchers) programme [121].…”
Section: Critical Literature Reviewmentioning
confidence: 99%
“…For further reading comprehension, Table 6 summarises the main applications and payloads identified by cluster. Urban thermal monitoring [111][112][113][114][115][116][117]121] Urban energy system inspection [110] Air quality control [122][123][124] Smart city [6,50,[125][126][127] Cadastral mapping [92]…”
Section: Critical Literature Reviewmentioning
confidence: 99%
“…The first test image was constituted by an aerial thermal image (size 480 × 640 pixels), representing the School of Engineering of Bologna University. It was part of the thermal aerial survey over the city of Bologna, held on 14 March 2016 in the framework of the ChoT (The challenge of remote sensing thermography as indicator of energy efficiency of buildings) project [32]. Only the most relevant characteristics of the survey are summarized here, and readers are referred to previous publications for further details [15,33].…”
Section: Aerial Thermal Imagementioning
confidence: 99%
“…Now, we analyze the performance of the ASR2 for MISR, that is more than one input image was available (we name our method as ASR2_m in the following). Figure 4a plots the increasing trends of the PSNR parameter of ASR2_m by increasing the number of input images in the range [2,32]. We observed that about 12 images were sufficient to get the best result.…”
Section: Experiments On Simulated Datamentioning
confidence: 99%
“…This district, located North in Bologna, has been chosen because it is the subject of energetic efficiency analysis in the frame of the ChoT project (The Challenge of remote sensing Thermography as indicator of energy efficiency of buildings) of the DICAM Dept. (Mandanici & Conte, 2016). The generated buildings' 3D model may in fact constitute another important factor in the evaluation of energy efficiency in this urban area.…”
Section: The Imagery Datasetmentioning
confidence: 99%